Prevalence of Dietary Supplement Use in Healthy Pre-School Chinese Children in Australia and China - Chen, Shu; Binns, Colin; Maycock, Bruce; Liu, Y.; Zhang, Y. (MDPI Publishing, 2014)
There is a growing use of dietary supplements in many countries including China. This study aimed to document the prevalence of dietary supplements use and characteristics of Chinese pre-school children using dietary supplements in Australia and China. A survey was carried out in Perth, Western Australia of 237 mothers with children under five years old and 2079 in Chengdu and Wuhan, China. A total of 22.6% and 32.4% of the Chinese children were taking dietary supplements in Australia and China, respectively. In China, the most commonly used dietary supplements were calcium (58.5%) and zinc (40.4%), while in Australia, the most frequently used types were multi-vitamins/minerals (46.2%) and fish oil (42.3%). In Australia, “not working”, “never breastfeed”, “higher education level of the mother” and “older age of the child” were associated with dietary supplement use in children. In China, being unwell and “having higher household income” were significantly related to dietary supplement usage. Because of the unknown effects of many supplements on growth and development and the potential for adverse drug interactions, parents should exercise caution when giving their infants or young children dietary supplements. Wherever possible it is preferable to achieve nutrient intakes from a varied diet rather than from supplements.